1995
DOI: 10.1192/bjp.167.5.679
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of a History of Childhood Sexual Abuse in Bulimia Nervosa

Abstract: Although those with CSA had greater comorbidity, it was not an important modifier of bulimic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 11 publications
1
13
1
2
Order By: Relevance
“…By contrast, nonspecific factors included childhood physical and sexual abuse, which were reported almost equally by both of the two psychiatric groups – a finding consistent with other studies [19, 20, 29, 33, 56, 57]. …”
Section: Discussionsupporting
confidence: 81%
“…By contrast, nonspecific factors included childhood physical and sexual abuse, which were reported almost equally by both of the two psychiatric groups – a finding consistent with other studies [19, 20, 29, 33, 56, 57]. …”
Section: Discussionsupporting
confidence: 81%
“…Several studies (Favaro, Dalle Grave, & Santonastaso, 1998;Garfinkel et al, 1996;Pribor & Dinwiddle, 1992;Steiger & Zanko, 1990) have reported a stronger link between CSA and eating disorders involving binging and purging rather than restricting behaviors, whereas other studies have not (Palmer et al, 1990;Schmidt, Tiller, & Treasure, 1993;Vize & Cooper, 1995). More severe bulimic symptoms have (Waller, 1992), and have not (Bushnell et al, 1992;Favaro et al, 1998;Sullivan, Bulik, Carter, & Joyce, 1995), been associated with abuse experiences. In terms of comorbidity, eating disorder patients in clinical samples who have experienced CSA have higher rates of disorders that are characterized by poor impulse control (Favaro & Santonastaso, 1997;Folsom et al, 1993;Sullivan et al, 1995;Waller, 1991Waller, , 1993.…”
Section: Introductionmentioning
confidence: 88%
“…For example, Waller (1992) found that more severe abuse characteristics (e.g., abuse involving force or a family member) were associated with a higher rate of bulimic behaviors in a clinical sample. However, two subsequent studies involving clinical samples have reported no such association (Sullivan, Bulik, Carter, & Joyce, 1995;Vize & Cooper, 1995). The differences in these findings may be due to methodological differences.…”
Section: Introductionmentioning
confidence: 52%